Eusk. "gorosti", sardinierazko "golostri", eta errusiar "xvorost". Ohar etimologikoa - Iván Igartua (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1999)
This three words (Basque gorosti, Sardinian golostri and Russian xvorost) have been said to be related by substratum links. In this paper the author reviews the different pieces of evidence that were adduced in favor of this connection and then develops an etymological proposal concerning Basque gorosti, supported by data mainly from onomastics. Within the framework of contemporary diachronic research and Basque morphological studies, this etymology may lead to the conclusion that substratum hypothesis is still plausible for the Basque/Sardinian lexical coincidence, though not as clear as it was before. On the other hand, the author tries to show that there are no sufficient grounds to accept the same explanation for the Russian (an Slavic) word.